PENENTUAN PANJANG REKAMAN DATA CURAH HUJAN UNTUK MENGGAMBARKAN KONDISI IKLIM DI KECAMATAN JATINANGOR - Irfan Ardiansah; Selly Harnesa Putri; Devi Maulida Rahmah (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2018)
System availability to access climatology data especially precipitation data is needed to facilitate a variety of interested parties to use it for analysis purpose. Theoritically, it is better to analyze about 30 years of data to describe the climatic condition in a region, but to determine the exact minimum length of optimum rainfall data, a linear regression formula Y = (4.30t x log(R))2 + 6 can be used. Jatinangor as developing region do not have any complete climate conditions data yet, so to get an idea of its climate condition a minimum precipitation data analysis is needed. Precipitation data of Jatinangor is available from years 1994 to 2010 with the presence of missing data from August 2005 to December 2007 due to equipment damage, so its necessary to assest the missing data using reciprocal method. After analysis is done, it showed that there certain month that are still not meet the minimum data length requirements, especially in dry months because a longer period of data would normalize the data and will become easier to perform calculations and data analysis to describe the climatic conditions in Jatinangor.